Impact ofremittances by foreign workers on economic growth and economic development / Fauziana Fauzi @ Mat Rawi - Fauzi @ Mat Rawi, Fauziana (Universiti Teknologi Mara Cawangan Kelantan and Penerbit UiTM, 2016)
Abstract—Foreign workers are a major source of work force in the development of the economy, whether it is for the country that imports or exports foreign workers. The contribution given by them not only gives a great impact to the development of the importing country, but it also gives a great contribution to the country exporting them i.e., decrease the unemployment issues in their country of origin. Migration process is usually associated with the money transfer issue, or also known as remittance, which actually means the outflow of money from one country to another. The outflow of money by foreign workers usually brings benefits to the exporting countries compared to the importing countries (Ajis, et al., 2014). Taylor et al., (1996) added that direct effects from the consequences of money outflow will increase fund and source of income as well as generate economic development especially for sending countries. Global studies on the effects of remittances to economic growth have shown mixed results (Ang, 2007). To achieve those results, various model and method had been used. Thus this study is attempted to discuss on the impact of remittances by foreign workers on economic growth and economic development focusing onthe issue, model and the method used